OPTIMALISASI INSTAGRAM SEBAGAI PLATFORM PEMASARAN RENGGINANG DAN KERIPIK SINGKONG DI DESA SUKABUNGAH - Arifin, Nasjwa Putri Syachrah; Putra, Purnama (Universitas Islam 45 Bekasi, 2024)
The advancement of digital technology presents opportunities for micro-enterprises to enhance their marketing efforts through social media platforms. This community service program focuses on the digitalization of marketing via Instagram as a strategy to expand market reach and improve the competitiveness of rengginang and cassava chips businesses in Sukabungah Village, Bojongmangu District, Bekasi Regency. The program aims to provide education and training for home-based entrepreneurs to effectively utilize social media in promoting their products. The implementation method consists of several stages, including an initial survey and observation of existing marketing conditions, an awareness session on the importance of digital marketing, and hands-on training. The training covers creating a business Instagram account, developing engaging content, and applying social media marketing strategies. The program is designed to equip participants with the skills to independently manage their Instagram accounts while leveraging features such as feed posts, stories, reels, and paid advertisements to enhance product visibility. The results indicate a significant improvement in participants' understanding and skills in utilizing social media as a marketing tool. Previously inactive in digital marketing, participants have now developed the ability to create and manage Instagram accounts effectively while implementing promotional strategies tailored to their target market. The sustainability of this program is expected to drive the digital transformation of small businesses, enhance competitiveness, and expand the market share of local products in the digital economy era.